Investigating the Impact of HTNV Infection on the Gut Microbiota of Wild-Type and NLRX1 Knockout Mice - Wenjie Sun; Yaxin Ding; Ziyu Liu; Shiyuan Hou; Danni Sun; Ruixue Ma; Huarui Kang; Xiaohan Ma; Jiayu Wang; Hongrui Mu; Yunhua Lv; Tianle Gu; et al. (Advanced Gut & Microbiome Research)
It is becoming increasingly clear that maintaining the equilibrium of gut microbiota homeostasis during viral infections, such as Hantaan virus (HTNV), is of paramount importance. In order to gain insight into the role of NOD-like receptors in the immune system, we conducted a comparative study between C57BL/6 and Nlrx1-/- mouse models to analyze changes in the gut microbiota after HTNV infection. Our findings revealed an increase in the ratio of Firmicutes to Bacteroides in Nlrx1-/- mice, suggesting a potential link to inflammation. In addition, a comprehensive analysis of serum metabolomics revealed that differential metabolites were mainly concentrated in amino acid metabolism and lipid metabolism. Amino acid metabolism mainly involves arginine, lysine, and histidine metabolism, while lipid metabolism is mainly related to glycerophospholipid metabolism and fatty acid synthesis. Analysis of the correlation between microbiota and metabolites revealed an inverse relationship between Bacteroidetes and metabolites related to glutamine metabolism, while Firmicutes were directly associated with these metabolites. Furthermore, we observed a negative correlation between the presence of Actinobacteria, Proteobacteria, and Patescibacteria and the metabolites related to polyunsaturated fatty acids (PUFAs). Our results demonstrate that HTNV infection causes changes in the composition of gut microbiota in both Nlrx1-/- and wild-type (WT) mice. Moreover, the fecal microbiota and serum metabolites of Nlrx1-/- mice display notable differences at various developmental stages. Investigating this further may help to improve our understanding of the pathogenesis of HTNV and provide potential therapeutic options.